Investigating the functionality of candidate susceptibility genes in ophthalmoplegic myasthenia gravis using patient-derived material - Moyakhe, Lihle Bayavuya (Department of Medicine, 2020)
Ophthalmoplegic myasthenia gravis (OP-MG) is a subphenotype of an autoimmune disease, myasthenia gravis (MG). This subphenotype described by our group is characterised by extraocular muscle (EOM) weakness which does not respond to standard immunosuppressive therapy whilst the non-ocular muscles do respond to treatment. OP-MG predominantly affects patients of African genetic ancestry and most commonly those with juvenile-onset. The cause of OP-MG is unknown. Previously, in efforts to understand the pathophysiology of this subphenotype, whole-exome sequencing was undertaken which identified amongst others a putatively functional multi-allelic deletion in the 5’ untranslated regulatory region of the ST8SIA1 gene. The most frequent deletion was c.-477_475 delCCC. The first aim of this thesis was to assess the functionality of this variant. To this end, in vitro promoter-reporter assays were performed after the delCCC deletion (MT) was created by site-directed mutagenesis of the wild-type (WT) promoter. Transient transfection assays showed that basal promoter activity of the MT promoter was lower than the WT promoter in the human fibroblast cell line (HT1080, p=0.031) but not in a mouse myoblast cell line (C2C12, p=0.33). Next, gene expression analysis was performed in opportunistically sampled orbital fibroblasts (n=5 controls, n= 2 OP-MG) and the endogenous expression levels of ST8SIA1 was determined under basal conditions and following treatment with homologous MG sera to mimic MG conditions. Although there was no significant difference in the basal ST8SIA1 expression levels in OP-MG ocular fibroblasts when compared to the control ocular fibroblasts (p=0.091), there were significantly lower ST8SIA1 expression levels in OPMG ocular fibroblasts in response to MG sera (p=0.024). Previous work by others also identified two other African specific gene variants in IL6R and TGFB1 which associated with OP-MG and in which luciferase reporter work showed functional implications. This thesis conducted the first examination of the endogenous expression levels of these genes in patientderived ocular fibroblasts. There was no difference in TGFB1 expression levels between OP- MG and control ocular fibroblasts under basal conditions or following treatment with MG sera (p>0.3). However, IL6R expression showed a similar trend to the luciferase reporter assays results in HT1080 cells. Both the OP-MG ocular fibroblasts tested harboured the 3’UTR IL6R c.*3043T>C variant, which was predicted to alter a putative miRNA binding site and showed a trend towards repression of IL6R expression in response to MG sera (p=0.083). In conclusion, although faced with the scarcity of sample tissue, we were able to use patient-derived ocular fibroblasts to validate previous genetic association studies and in vitro assays. Although the ocular fibroblasts are not EOM, they are both specialised tissue existing in the same microenvironment. Since MG sera modulate the expression of ST8SIA1 and IL6R differently between OP-MG and controls, our findings suggest that these genes may play a role in the OP-MG pathogenesis. Larger sample sizes are required for a more accurate representation of endogenous gene expression within these cell lines as the sample size is a factor when determining the significance of data. This is, however, a challenge due to the scarcity and unavailability of EOM for cell culture.